First metatarsal extracapsular osteotomy to treat moderate hallux valgus deformity: the modified Wilson-SERI techinique - Touloupakis, Georgios; Ghirardelli, Stefano; Del Re, Matteo; Indelli, Pier Francesco; Antonini, Guido (Acta Biomedica Atenei Parmensis, 2021)
From February 2017 to December 2018, 20 patients had undergone the proposed modified Wilson-SERI osteotomy technique, for moderate hallux valgus. The mean age of patients was 58,25 years (range 19 to 78). The hallux valgus angle (HVA), the intermetatarsal angle between first and second metatarsal bone (IMA) and the distal metatarsal articular angle (D.M.A.A) were measured. The feet were assessed based on the scoring system used by Broughton and Winson and by the American Orthopedic Foot and Ankle Society (AOFAS) hallux-metatarsophalangeal-interphalangeal scale. All twenty one patients were followed up postoperatively for a minimum of 12 months. The mean HVA angle decreased significantly from 31,1° before surgery (range 22.9°-40°SD 5.0) at 11,2° (range 2.5° to 22.0°SD 5.3) at twelve months follow up. The mean IMA angle decreased significantly from 12,5° (range 8.0°-18.6°SD 3.8) before surgery at 7,4° (range 3.4°-14.0°SD 2.5) at twelve months follow up. The mean DMMA angle decreased significantly from 15.1° (range 5.3° to 20.0°SD 4.4) before surgery at 7,4 °(1.5°- 10.7°SD 2.5) at twelve months follow up. The mean score according to the AOFAS forefoot was increased from 22,1 (range 13-30 SD 5.0) to 88,2 (Range 77-96 SD 5.2) (p